Prenatal Screening Characteristics of Edwards’ Syndrome and Patau’s Syndrome in the First Trimester at the National Hospital of Obstetrics and Gynecology - Thi Trang, Nguyen; Danh Cuong, Tran; Thi Quynh, Do; Van Nga, Vu; Minh Thuy, Han; Toan Anh, Ngo; Hoang Phi, Nguyen; Thi Minh Phuong, Le (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2023)
Edwards and Patau syndromes are severe genetic abnormalities. The consequences of these syndromes are often fatal in the fetus and neonate. Prenatal screening for these syndromes is important for early detection of birth defects. 212 medical records of pregnant women with normal pregnancies were selected using convenience sampling. Selection of 34 cases of Edwards or Patau pregnancy using a total sampling technique. We conducted a descriptive retrospective study to describe and compare various markers related to prenatal screening to establish the most appropriate diagnostic criteria. A history of spontaneous abortion is associated with an increased risk of subsequent pregnancies with Edwards' syndrome or Patau's syndrome. The nuchal translucency value was mainly concentrated below 2 mm, lower than the values observed in Trisomy 18 and 13 cases, predominantly in the 2-3 mm range. A threshold of 2.5 mm for nuchal translucency measurement had the highest detection rate for Edwards and Patau syndromes, and abnormal fetal heart rate was most commonly observed in trisomy cases on ultrasound examination. The MoM fβ-hCG concentration in the Edwards and Patau groups was predominantly concentrated in the low range (≤1), while the normal group showed a higher concentration in the range of 1-3. The MoM PAPP-A concentration in the normal group was commonly found in the range of 0.5-1, which was higher compared to the trisomy group. Keywords: Edwards Syndrome, Patau Syndrome, Prenatal screening.